Determination of the electrical conductivity of human liver metastases: impact on therapy planning in the radiofrequency ablation of liver tumors. (February 2017) - Zurbuchen, Urte; Poch, Franz; Gemeinhardt, Ole; Kreis, Martin E; Niehues, Stefan M; Vahldieck, Janis L; Lehmann, Kai S
Background: Radiofrequency ablation is used to induce thermal necrosis in the treatment of liver metastases. The specific electrical conductivity of a liver metastasis has a distinct influence on the heat formation and resulting tumor ablation within the tissue. Purpose: To examine the electrical conductivity σ of human colorectal liver metastases and of tumor-free liver tissue in surgical specimens. Material and Methods: Surgical specimens from patients with resectable colorectal liver metastases were used for measurements (size of metastases <30 mm). A four-needle measuring probe was used to determine the electrical conductivity σ of human colorectal liver metastasis (n = 8) and tumor-free liver tissue (n = 5) in a total of five patients. All measurements were performed at 470 kHz, which is the relevant frequency for radiofrequency ablation. The tissue temperature was also measured. Hepatic resections were performed in accordance with common surgical standards. Measurements were performed in the operating theater immediately after resection. Results: The median electrical conductivity σ was 0.57 S/m in human colorectal liver metastases at a median temperature of 35.1℃ and 0.35 S/m in tumor-free liver tissue at a median temperature of 34.9℃. The electrical conductivity was significantly higher in tumor tissue than in tumor-free liver tissue ( P  = 0.005). There were no differences in tissue temperature between the two groups ( P  = 0.883). Conclusion: The electrical conductivity is significantly higher in human colorectal liver metastases than in tumor-free liver tissue at a frequency of 470 kHz.